A Fregean Semantics for Number Words - Rothstein, Susan (Proceedings of the Amsterdam Colloquium, 2013)
This paper proposes a Fregean semantics for cardinal numbers , analysing them as properties (Chierchia 1985). A cardinal numeral can occur at the predicative type denoting a set, and at an argument type denoting the individual correlate of a set. Lexical powers like hundred and thousand denote multiplicands and are of a different type from other cardinals.